Human Peron and Culture: A Study Based on ‘The Church in the Modern World’ ( Gaudium et Spes) - Gerard de Rosairo, E.A. (University of jaffna, 2018)
This presentation is based on a study on the pastoral constitution, The Church In The Modern World’, (Gaudium et Spes/GS) Chapter 2 in Vatican Council II’ The Conciliar and post- Conciliar Documents. The pivotal point of total presentation is human person himself or herself in his or her historical, cultural context for, as it is stated “man himself who must be saved; it is humankind that must be renewed. It is human, therefore, who is key to this discussion, human person considered whole and entire, with body and soul, heart and conscience, mind and will”. It is observed that the living conditions of modern human persons have been so profoundly changed in human history. In the context of ‘new age/culture’ the emphasis is laid on developing a proper culture, for human person can fully develop into full humanity only through culture. While, it highlights the birth of a new culture and its impact on humans, it emphasizes also on the need to acknowledge the positive values of modern culture and the importance of human wisdom. It is in this context the emphasis also falls on developing a true culture recognizing the rights of every one . It urges the readers to focus on cultural education to realize one’s full humanity in a pluralistic context. One of the most creative parts of the Constitution is its reflections on culture (Part II, Chapter 2). This section seeks to synthesize culture with Christian faith. However, it is to be noted that, “the reading of the time “, key emphasis of the GS, concerns all human persons of good will; it is not a monopoly of Christians. Recognizing the religious freedom and supporting the basic human aspirations towards greater equality, GS seeks to promote human freedom and responsibility in all spheres of life. Basic culture attainments are not only the right, but also the duty, of each human person to possess. Without distinction of race, sex, or creed, each person has an inalienable right and duty to literacy and higher education, according to his/her capacities. Freedom of thought, freedom of expression and enquiry must be ensured for everyone.
Keywords: Relational dimension; Multi culture; Integralism; Community; Stewardship